Dinoflagellate cyst distribution during the Middle Eocene in the Drake Passage area: paleoceanographic implications - González Estebenet, María Sol (2014)
The middle-late Eocene (45-36 Ma) dinoflagellate cyst distribution in high latitudes of the Southern Hemisphere has been explained by a surface ocean circulation pattern characterized by extensive subpolar gyres around Antarctica. Based on global paleoclimate models it has been proposed that these surface ocean gyres might favored the development of an Antarctic-endemic dinoflagellate cyst assemblage, which was consistently abundant until the end of the Eocene. During the late Eocene the deepening of the Tasman Gateway and the Drake Passage would have generated a circumpolar water flow responsible for the disruption of the local gyre system and the subsequent extinction of the endemic assemblage. Some authors have recently suggested that during the middle Eocene shallow water flows had already developed through incipient openings of the Tasman Gateway and the Drake Passage. In this review we have compared the middle Eocene dinoflagellate cysts assemblages dominated by the Antarctic-endemic species from localities of the Drake Passage area and performed a multivariate analysis to evaluate this hypothesis. Our results point out a clear differentiation between localities to the north and south of what now is the Drake Passage. While localities from the Antarctic Peninsula and Scotia Sea would had been affected by Antarctic surface waters, the Austral Basin would had been flooded by Antarctic waters together with Pacific waterflows developed through an incipient Drake Passage during the middle Eocene.